Adaptive Changes on the Dominant Shoulder of Collegiate Handball Players—A Comparative Study. Issue 3 (March 2019) - Vogler, Tim; Schorn, Dominik; Gosheger, Georg; Kurpiers, Nico; Schneider, Kristian; Rickert, Carolin; Andreou, Dimosthenis; Liem, Dennis
Abstract : Abstract: Vogler, T, Schorn, D, Gosheger, G, Kurpiers, N, Schneider, K, Rickert, C, Andreou, D, and Liem, D. Adaptive changes on the dominant shoulder of collegiate handball players—A comparative study. J Strength Cond Res 33(3): 701–707, 2019—Handball players are susceptible to adaptive bony and soft-tissue changes of the dominant shoulder. Our goal was to compare the glenohumeral range of motion and posterior capsule thickness between the dominant and nondominant arm of throwing athletes and between the dominant arm of nonthrowers and throwing athletes. Twenty-three collegiate handball players and 23 nonthrowing athletes underwent an examination of the dominant and the nondominant shoulder. Humeral retroversion and posterior capsule thickness were assessed with an ultrasound examination, whereas external rotation and internal rotation were determined with a digital inclinometer. The dominant shoulder of handball players had a significantly higher external rotation compared with their nondominant shoulder and the dominant shoulder of nonthrowing athletes. Furthermore, the dominant shoulder of handball players had a significantly lower internal rotation compared with their nondominant shoulder, with no differences compared with the dominant shoulder of the nonthrowing athletes. There was a trend for an increased posterior capsule thickness and an increased humeral retroversion between the dominant and the contralateral shoulder of handball players. Moreover, we found a significant increase in the capsule thickness of the dominant shoulder of throwing athletes compared with the dominant shoulder of nonthrowers. However, there were no differences in humeral retroversion. Our analysis suggests that a comparison of the dominant shoulder of overhead throwing athletes with the dominant shoulder of nonthrowing athletes might be more appropriate than the comparison of the dominant and the nondominant shoulder to evaluate the adaptive changes on the dominant side.